KUALITAS MUTU SAYUR KASEPAK (KANGKUNG, SELADA, DAN PAKCOY) DENGAN SISTEM BUDIDAYA AKUAPONIK DAN HIDROPONIK - Laela Endah Rahmadhani; Laily Ilham Widuri; Parawita Dewanti (JURNAL AGROTEKNOLOGI, 2020)
Aquaponic is considered one of alternative culture system to improve production and quality of leafy vegetables by combining soil less culture and fish farming. Utilization of fish manure contained in waste water provides nutrient sources for growing plants. Three kinds of leafy vegetables including water spinach (Ipomoea aquatica F.), green coral lettuce (Lactuca sativa L.), and bok choi (Brassica rapa L.) were grown using both aquaponic and hydroponic system at the Green House in Serut village, Panti District, Jember Regency, from April to June 2019. Productions of each leafy vegetable were evaluated on both culture systems. Water spinach represented 29.12% higher production in aquaponic than hydroponic system, shown by significant value in plant height, number of leaves, root volume, and leaf fresh weight. Otherwise, bok choi production displayed 17.03% increased in hydroponic than aquaponic system. However, leaf production of lettuce was not significant between hydroponic and aquaponic system. Lettuce production in aquaponic only 1.90% lowest than hydroponic system indicated that lettuce was appropriate to cultivate in both farming systems. Keywords: aquaculture, Brassica rapa L., leaf fresh weight, Ipomoea aquatica F., Lactuca sativa L., soil less culture